PERAN BADAN PEMBERDAYAAN PEREMPUAN DAN KELUARGA BERENCANA DALAM MENANGANI KASUS PERDAGANGAN MANUSIA KABUPATEN SAMBAS - D. Hafiz Saprizal E.42008003 (FISIP Universitas Tanjungpura Pontianak, 2012)
This script intend to find solutions to problems faced in dealing with cases of human trafficking in district of Sambas. Using qualitative research methods with a descriptive apprpach. The results of this study indicate the factors that influencing the rise of human trafficking crimes in the district is the high poverty, fower jobs available, low levels of education, early marriage, high accessibility from the neighbour’s countrie, influence of the culture, the promising migrant’s business migrantsKeyword : rules and human trafficking